2020
DOI: 10.1016/j.annonc.2020.08.1100
|View full text |Cite
|
Sign up to set email alerts
|

984P Sorafenib plus hepatic arterial infusion chemotherapy versus sorafenib alone for advanced hepatocellular carcinoma with major portal vein tumor thrombosis (Vp3/4): A randomized phase II trial

Abstract: Background: Combination of checkpoint inhibitors (CPIs) with anti-angiogenic agents are emerging as potential novel treatment options of hepatocellular carcinoma (HCC).Here we assessed the efficacy and safety of C+A in patients (pts) with advanced HCC.Methods: This phase II study was conducted at 25 study sites in China. Pts with advanced HCC, treatment-naive or failure to sorafenib or donafenib were enrolled. Pts received intravenous C 200 mg every 2 weeks plus A 250 mg qd. The primary endpoint was objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our study, 36.6% of patients received HAIC treatment along with alternating therapy with LEN. Recently, Wang X et al reported that the prognosis of patients treated SORA plus HAIC prolonged OS compared treated with SORA monotherapy for advanced HCC [ 19 ]. Moreover, Shi et al reported that HAIC is suitable for large unresectable HCC, such as high tumor burden (multinodular type, huge type, and invasive growth type) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 36.6% of patients received HAIC treatment along with alternating therapy with LEN. Recently, Wang X et al reported that the prognosis of patients treated SORA plus HAIC prolonged OS compared treated with SORA monotherapy for advanced HCC [ 19 ]. Moreover, Shi et al reported that HAIC is suitable for large unresectable HCC, such as high tumor burden (multinodular type, huge type, and invasive growth type) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%